Farmers’ awareness and perceptions of the new farm laws 2020 in India: Empirical evidence from a household survey - Kumar, Anjani; Sonkar, Vinay Kumar; Bathla, Seema (Indian Society of Agricultural Economics, 2021)
In 2020, the Union government enacted three new farm laws to address the structural weaknesses inherent in the sale, marketing and stocking of agriculture produce in the regulated/wholesale markets. This has provoked serious discussion, criticism and even protest, especially in Punjab and Haryana to the extent that the Supreme Court put them on hold for some time. This paper assesses the farmers’ awareness and perceptions about these laws based on a large survey of households carried out during 2020 across five eastern states – Bihar, Eastern Uttar Pradesh, Jharkhand, Odisha, and West Bengal. The probit and multinomial regression models are used to examine the socio-economic factors that influence the farmers’ awareness and perceptions about usefulness of the ordinances. The findings reveal that about 50 per cent agricultural households in eastern India are aware about the new farm laws; they hardly possessed any knowledge about the contents therein. Several socio-economic factors among farm households correlate significantly with the awareness of the new farm laws and holding opinions about their usefulness. These include the size of landholding, level of education of the household head, awareness of government programmes, and visits to Kisan Melas. The findings of the study suggest that the governments (centre and state) should make efforts to demystify the ordinances to farmers, traders and other stakeholders and generate confidence among them about a competitive agri-marketing environment.